Preparation of activated carbon from empty fruit bunch for hydrogen storage - Md. Arshad, S. H. (Elsevier Ltd, 2016)
There are many advantages associated with the use of hydrogen as clean fuels, thus there is a need to search for good hydrogen adsorbents. Activated carbon (AC) from various sources has been tested as hydrogen adsorbents, with the exception of AC produced from empty fruit bunch (EFB). The aim of this study is to produce AC from EFB obtained in Malayisa, followed by testing on its hydrogen storage capacity. The AC samples were activated using physical and chemical processes. The total surface areas (SBET) and microporous structures of the ACs produced were in the range of 305–687 m2/g and up to 94%, respectively. The hydrogen storage capacity was studied at constant temperature, 77K and pressure from ambient pressure up to 100 bar. The hydrogen uptake increased occasionally from 0 bar to 20 bar and decreased above 20 bar. EFB activated with 2M KOH demonstrated maximum hydrogen adsorption capacity with 2.14 wt% hydrogen uptake at 20 bar. More research is needed to improve the hydrogen adsorption capacity on AC, and to determine its potential applications other than mobile applications.